Determinan Perilaku Merokok Pada Individu Dengan Gangguan Kesehatan Mental Di Indonesia: Sebuah Tinjauan Naratif - Mutiara Nisa; Langen Nidhana Meisyalla (Shofanah Media Berkah, 2026)
Indonesia recorded an adult smoking prevalence of 30.4% in 2024, with a substantial gender disparity, reaching 59.7% among men compared to 1.2% among women. Amid this tobacco epidemic, individuals with mental health disorders consistently exhibit smoking rates two to four times higher than those of the general population, yet they have received limited attention within Indonesia’s national tobacco control agenda. This narrative review aims to synthesize empirical evidence on the determinants of smoking behavior among individuals with mental health disorders in the Indonesian context by integrating relevant global literature and examining its implications for the national mental healthcare system. A literature search was conducted using PubMed/MEDLINE, PsycINFO, Scopus, and Google Scholar with keywords related to smoking behavior, mental health disorders, and Indonesia. Studies published between 2014 and 2025 were prioritized, while seminal publications outside this period were included when considered substantially relevant. The findings indicate that the determinants of smoking behavior operate across four interrelated levels: (1) the biological–psychiatric level, including the nicotine self-medication hypothesis, diagnostic type and severity, and pharmacokinetic interactions with antipsychotic medications; (2) the psychosocial level, encompassing stress as a trigger, maladaptive coping strategies, and inadequate social support; (3) the structural–institutional level, including Indonesia’s mental health treatment gap, the absence of integrated smoking cessation protocols, and the widespread availability of tobacco products around mental health facilities; and (4) the sociocultural level, involving constructions of masculinity, gender norms, and family dynamics. Indonesia presents additional challenges due to weak tobacco control policies—as the only ASEAN country that has not ratified the WHO Framework Convention on Tobacco Control (WHO FCTC)—and the unequal distribution of mental health professionals, which remains concentrated on Java Island. Smoking behavior among individuals with mental health disorders in Indonesia should therefore not be viewed solely as an individual choice but rather as the outcome of complex interactions among neurobiological factors, psychological distress, systemic healthcare limitations, and deeply rooted sociocultural norms. Integrating smoking screening and smoking cessation interventions into mental health services should become an urgent policy priority to improve both mental and physical health outcomes.